1988
DOI: 10.1039/c39880000741
|View full text |Cite
|
Sign up to set email alerts
|

Organo-phosphorus–selenium heterocycles

Abstract: Reaction of selenium with (PhP)5, or Li2Se with PhPC12, gives a reactive intermediate (I) which undergoes reaction with acetone or CS2 to give new organo-phosphorus-selenium heterocycles which have been characterised by X-ray crysta I log ra p hy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 2 publications
2
52
0
2
Order By: Relevance
“…34 This early work by Paul Wood also ultimately led via some convoluted routes to our interest in group 16 Peri substitution is hard to direct synthetically and after developing the naphthalene systems we found that acenapthene systems are synthetically much more readily prepared and provide an excellent backbone or molecular scaffolding for studying weak interactions between heavier elements. 37 In Figure 5 Upper The X-ray structure of a typical ionic C.-T. 'extended spoke' adduct, middle a typical 'see-saw' adduct formed from Nap(EPh)2. And lower intramolecular packing in seesaw adducts.…”
Section: Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…34 This early work by Paul Wood also ultimately led via some convoluted routes to our interest in group 16 Peri substitution is hard to direct synthetically and after developing the naphthalene systems we found that acenapthene systems are synthetically much more readily prepared and provide an excellent backbone or molecular scaffolding for studying weak interactions between heavier elements. 37 In Figure 5 Upper The X-ray structure of a typical ionic C.-T. 'extended spoke' adduct, middle a typical 'see-saw' adduct formed from Nap(EPh)2. And lower intramolecular packing in seesaw adducts.…”
Section: Equationmentioning
confidence: 99%
“…The early organic reactivity was tested using a solution of (1) in scheme 9 and showed immediate promise with two new organo -P-Se heterocycles being isolated and characterized crystallographically. 37 Emboldened by our exciting results I submitted abstracts on both M-S-N and P-Se chemistry to the 5 th Inorganic Rings International Symposium in Amherst. Whilst my presentation on M-S-N chemistry went well I was rather dismayed to sit through a lecture by Karagiosoff which summarized at least half of my groups work in the area.…”
Section: Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 WR is used in the synthesis of seleniumcontaining organic compounds and P-Se heterocycles. 2 Woollins and co-workers initially prepared WR from the pentamer (PhP) 5 , 3 which is an air-sensitive compound with a lingering stench. For this reason, they have developed a new method preparing WR producing material of high purity in high yield.…”
Section: Introductionmentioning
confidence: 99%